Analisis Manajemen Fleet Pada Kegiatan Produksi Batu Andesit Dalam Penerapan Metode Antrian di PT Koto Alam Sejahtera, Kabupaten Lima Puluh Kota - Yuliana Safitri; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. PT Koto Alam Sejahtera is a private company engaged in the mining business, especially the Andesite stone. In the process of transporting andesite stones to the crusher, there is a dump truck queue and a long stand-by time on the dump truck, this can cause the productivity of the tool to be small so that the andesite stones production target of 30.000 ton/month is not achieved. This is due to the inefficient working time of mechanical devices. This production target was not achieved due to improper combination of tools, road width and road grade that did not meet the standards, causing queues or waiting times for transport on the front loading and at some road points. One way to achieve the production target is needed fleet management accordingly. Based on the results of the study, it can be concluded that the productivity of excavator Hitachi ZX-350 is 232,61 ton/hour and the productivity of dump truck Mitsubishi Fuso 220 PS is 47,30 ton/hour. The composition of the available equipment is 1 unit of excavator serving 5 units of dump trucks. Efforts to reduce the queuing time are to make improvements to the composition of the equitment MF=1. Fleet settings are based on method Antrian, that is 1 unit of loading equipment serves 4 units of transport equipment with a production of 38.485 ton/month.Keywords: Fleet Management, Method Queue, Match Factor, Production, Productivity, Dump Truck